-5m+7(8-11m)=-94-7

Simple and best practice solution for -5m+7(8-11m)=-94-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5m+7(8-11m)=-94-7 equation:


Simplifying
-5m + 7(8 + -11m) = -94 + -7
-5m + (8 * 7 + -11m * 7) = -94 + -7
-5m + (56 + -77m) = -94 + -7

Reorder the terms:
56 + -5m + -77m = -94 + -7

Combine like terms: -5m + -77m = -82m
56 + -82m = -94 + -7

Combine like terms: -94 + -7 = -101
56 + -82m = -101

Solving
56 + -82m = -101

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + -82m = -101 + -56

Combine like terms: 56 + -56 = 0
0 + -82m = -101 + -56
-82m = -101 + -56

Combine like terms: -101 + -56 = -157
-82m = -157

Divide each side by '-82'.
m = 1.914634146

Simplifying
m = 1.914634146

See similar equations:

| 4x-9/2=8 | | 7x-(11x^2+9x)= | | 2x+21-x+21=2 | | y=-0.00211x^2+1.06x | | 9x^2+9y^2+6x-12y+1=0 | | 6-m/6-1=0 | | -22=22-5x | | 6-m/6-1=2 | | x^2+-6x+99=121 | | 80.25-70.25= | | d/dx(ln(e^2x))) | | X/6(-9)=3 | | 5.5/22 | | 5000=0.15+250n | | 33=-3(x-7) | | 21=0.75 | | 0.15=250x+5000 | | 4=7x+-8+-3x | | P+258=-4p+8 | | 42=5x+8 | | 4(x-2)2=36 | | 2000+x=3300-0.15 | | 7(2-7x)=259 | | (8w+4x)(5w-6x)=0 | | 2000+x=3300+0.15 | | Y-25=3y+5 | | 13-7r=24 | | 15=3t-5-8t | | (15mn)(-4m+6mn-10n)= | | y-1=3/4(x-2) | | 2(-5x+6)=72 | | (7w-5)(6w+6y-1)= |

Equations solver categories